Organization Design And Behavior In Forming A Productive Work Culture At SDIT Haji Jalaluddin - Irsyad, Muhammad; Junaidi, Junaidi (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2024)
Organizational design and behavior have a vital role in shaping a productive work culture at SDIT Haji Jalaluddin. In the context of education, a good organizational design should support the vision and mission of the school and provide a clear structure for the implementation of daily tasks. SDIT Haji Jalaluddin implements a flexible yet structured organizational structure, with each teacher and staff having clear roles and responsibilities. This facilitates coordination and collaboration between team members, so they work more efficiently and effectively. In addition, individual and group behavior greatly influences the work culture in the school. SDIT Haji Jalaluddin encourages positive behaviors such as cooperation, good communication, and a sense of responsibility. The school also instills Islamic values in every aspect of its operations, which form the basis of a productive and harmonious work culture. Character development through self-development and training programs is a key focus, ensuring every staff member has the skills and attitudes that support productivity. By combining efficient organizational design and positive work behaviors, SDIT Haji Jalaluddin succeeds in creating a work environment conducive to high educational goals. This environment not only improves individual performance but motivates the entire team to work harder for mutual success. Thus, the organizational design and behaviors implemented at SDIT Haji Jalaluddin are key to shaping a productive and sustainable work culture. This research aims to explore how organizational design and behaviors play an important role in shaping a productive work culture at SDIT Haji Jalaluddin by using a qualitative approach to the case study method, involving direct observation, interviews with teachers and employees, and analysis of internal school documents. Keywords: Education Organisation Design, Productive Work Culture in SDIT, Positive Work Behaviour in Schools